2020
DOI: 10.25518/0037-9565.9763
|View full text |Cite
|
Sign up to set email alerts
|

Approche diachronique de la flore des bassins fermés halomorphes de la région d’Oran (N-O Algérie)

Abstract: Cette étude est une approche diachronique d’étude de la flore et de la végétation des zones humides de la région d’Oran. Son but est de proposer une liste actualisée de la flore présente au niveau des ceintures des cinq bassins fermés d’Oran (la grande sebkha d’Oran, dayat Morsli, Oum El-Ghelaz, le lac Télamine et les salines d’Arzew). Cela nous permettra de d’identifier les changements que cette flore a subi et d'apprécier par conséquent la dynamique de la végétation locale à la lumière des conditions écologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…(Family of Lamiaceae) is a perennial, low-growing sub-shrub, native to the Mediterranean region. It is commonly found in a variety of habitats, including open forests, rangelands, plains, and low-elevation mountainous areas within the semi-arid zones of North Africa and southern Europe [19]. A previous study indicated that B. hirsuta seeds exhibited a remarkable germination capacity across a wide temperature range (5 to 30 • C) under controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(Family of Lamiaceae) is a perennial, low-growing sub-shrub, native to the Mediterranean region. It is commonly found in a variety of habitats, including open forests, rangelands, plains, and low-elevation mountainous areas within the semi-arid zones of North Africa and southern Europe [19]. A previous study indicated that B. hirsuta seeds exhibited a remarkable germination capacity across a wide temperature range (5 to 30 • C) under controlled laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…is a leaf succulent halophyte that grows in arid and semiarid saline habitats or salt marshes (Hameed et al, 2012). This plant species is widely distributed in halomorphic ecosystems in Algeria (Bahi et al, 2020). It has a strong ability to accumulate and sequester NaCl (Hameed et al 2012), and shows the capacity to accumulate large amounts of heavy metals in its tissues without symptoms of toxicity.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%